Differential regulation of two FLNA transcripts explains some of the phenotypic heterogeneity in the loss‐of‐function filaminopathies. Issue 1 (2nd November 2017) - Jenkins, Zandra A; Macharg, Alison; Chang, Cheng‐Yee; van Kogelenberg, Margriet; Morgan, Tim; Frentz, Sophia; Wei, Wenhua; Pilch, Jacek; Hannibal, Mark; Foulds, Nicola; McGillivray, George; Leventer, Richard J; et al.
Abstract: Loss‐of‐function mutations in the X‐linked gene FLNA can lead to abnormal neuronal migration, vascular and cardiac defects, and congenital intestinal pseudo‐obstruction (CIPO), the latter characterized by anomalous intestinal smooth muscle layering. Survival in male hemizygotes for such mutations is dependent on retention of residual FLNA function but it is unclear why a subgroup of males with mutations in the 5′ end of the gene can present with CIPO alone. Here, we demonstrate evidence for the presence of two FLNA isoforms differing by 28 residues at the N‐terminus initiated at ATG +1 and ATG +82 . A male with CIPO (c.18_19del) exclusively expressed FLNA ATG +82, implicating the longer protein isoform (ATG +1 ) in smooth muscle development. In contrast, mutations leading to reduction of both isoforms are associated with compound phenotypes affecting the brain, heart, and intestine. RNA‐seq data revealed three distinct transcription start sites, two of which produce a protein isoform utilizing ATG +1 while the third utilizes ATG +82 . Transcripts sponsoring translational initiation at ATG +1 predominate in intestinal smooth muscle, and are more abundant compared with the level measured in fibroblasts. Together these observations describe a new mechanism of tissue‐specific regulation of FLNA that could reflect the differing mechanical requirements of these cell types during development. Abstract : Loss‐of‐function mutations in the X‐linked gene FLNA lead to abnormal neuronal migration, vascular and cardiac defects and congenital intestinal pseudo‐obstruction (CIPO), characterised by anomalous intestinal smooth muscle layering. Males presenting with CIPO alone, are associated with variation in one of two identified transcripts differing by 28 residues at the N‐terminus which is predominately expressed in intestinal smooth muscle. These observations describe a new mechanism of tissue‐specific regulation of FLNA.